2019
DOI: 10.1017/s002193201900052x
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner abuse among couples during pregnancy and its predictors as reported by pregnant women visiting governmental health care centres in Tabriz, Iran

Abstract: Little is known about intimate partner abuse (IPA) among couples during pregnancy in Iran. This study aimed to compare the rates of IPA by pregnant women towards their husbands (perpetration), and women’s experience of IPA from their husbands (victimization) and determine the predictors of the two behaviours. The cross-sectional study was conducted on 525 pregnant women at 24–30 weeks of gestation visiting governmental health care centres/posts in Tabriz, Iran, in 2014. The study sample was selected using rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
3
5
0
Order By: Relevance
“…The results of this study showed that psychological aggression had the highest prevalence in IPV against young women. This finding is consistent with other studies in Iran [31][32][33]. Also, according to obtained results by Martin et al in North Carolina, pregnancy was not associated with significant increases in the rates of physical assault or injuries, but psychological aggression was increased [34].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study showed that psychological aggression had the highest prevalence in IPV against young women. This finding is consistent with other studies in Iran [31][32][33]. Also, according to obtained results by Martin et al in North Carolina, pregnancy was not associated with significant increases in the rates of physical assault or injuries, but psychological aggression was increased [34].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, prevalence of overall IPV was 63%. Relatively similar results have been reported from other cities of Iran [31,32], which can be attributed to the use of similar instrument (CTS2) or similar setting. Envuladu et al has been reported IPV 31.8% in Nigeria by semi structured interviewer administered questionnaire [15].…”
Section: Discussionsupporting
confidence: 85%
“…Sarayloo et al [35], reported a domestic violence rate of 46 %. In the research by Bahrami et al [36], the prevalence of violence committed by a spouse was reported as about 67 %. Musa et al [37] reported the prevalence of violence committed by a partner during pregnancy as 39.81 %.…”
Section: Discussionmentioning
confidence: 96%
“…Further, the reviewed studies focus on the underprivileged areas of Iran with different ethnicities; However, the current study was conducted in the city of Tabriz, which is one of the metropolises of Iran. The only study conducted in Tabriz was by Bahrami et al [36], while the difference in the rate of domestic violence against pregnant women in the two studies could be due to differences among the participants and research tools. The mean age of pregnant women who participated in their study was 25.8; while the mean age of participants in this study was 30.6.…”
Section: Discussionmentioning
confidence: 99%
“…However, if their figures are compared with the existing data in the literature, the same trend is observed. Specifically, in Iran, the prevalence of domestic violence during pregnancy during the pandemic was 35.2% in our review [ 39 ], much lower than the prevalence of 67–70% found in a 2020 study in the same city [ 76 ]. In Ethiopia, while the prevalence of IPV during pregnancy was 7.1% in our review, it was as high as 20–35% in other recent studies from this country [ 35 , 77 ].…”
Section: Discussionmentioning
confidence: 55%